Análisis estructural mediante elementos finitos de edificaciones con estructuras de acero de ductilidad limitada en la ciudad de Machala. - Segarra Zea, Fernando Xavier (Machala : Universidad Técnica de Machala, 2024)
This project addresses the non-linear static (pushover) analysis of a two-storey building with steel sections and limited ductility, in order to assess its structural response under gravitational and seismic loads. To this end, a detailed bibliographic review was initially carried out on the behaviour of steel structures and their non-linear analysis methods, with particular focus on the parameters influencing plasticity and permissible displacements. Subsequently, a finite element model of the building was developed, incorporating its actual geometry, the constitutive properties of the material, support conditions and the various load combinations. With the progressive application of lateral loads, the formation sequences of plastic hinges were obtained, and the most vulnerable areas were identified, paying special attention to the potential occurrence of brittle failures. Furthermore, through multi-modal analysis, it was possible to calculate the capacity curves for the most significant vibration modes and determine the ultimate displacements. The results made it possible to specify the necessary levels of strength and stiffness for an adequate performance of the building under seismic demands, as well as to propose reinforcement or redesign measures in critical areas. In this way, the study contributes to improving structural safety, reducing the risk of significant damage and extending the service life of buildings with steel sections and limited ductility.
En este proyecto se aborda el análisis no lineal estático (pushover) de una vivienda de dos plantas con perfiles metálicos y ductilidad limitada, con el fin de evaluar su respuesta estructural frente a cargas gravitatorias y sísmicas. Para ello, se realizó inicialmente una revisión bibliográfica detallada sobre el comportamiento de estructuras de acero y sus métodos de análisis no lineal, con especial atención a los parámetros que influyen en la plasticidad y los desplazamientos admisibles. Posteriormente, se elaboró un modelo en un software de elementos finitos que incluyó la geometría real del edificio, las propiedades constitutivas del material, las condiciones de apoyo y las diferentes combinaciones de carga. Con la aplicación progresiva de cargas laterales, se obtuvieron las secuencias de formación de rótulas plásticas y se identificaron las zonas más vulnerables, prestando especial atención a la posible aparición de fallas frágiles. Además, mediante análisis multimodal, fue posible calcular las curvas de capacidad en los modos de vibración más relevantes y determinar los desplazamientos últimos. Los resultados obtenidos permitieron precisar los niveles de resistencia y rigidez necesarios para un desempeño adecuado de la vivienda bajo demandas sísmicas, así como proponer medidas de refuerzo o rediseño en las zonas críticas. De esta manera, se contribuye a mejorar la seguridad estructural, reduciendo el riesgo de daños significativos y prolongando la vida útil de edificaciones con perfiles metálicos y ductilidad limitada.
Keywords: ANALISIS NO LINEAL ESTATICO; DUCTILIDAD LIMITADA; PERFILES METALICOS; ANALISIS MULTIMODAL